The use of technology for the growth of the sustainability concept inside community - De Moraes, Thiago Matheus Martins [UNESP]; De Lima Viveiros, Henrique Amon [UNESP]; Jacintho, Felipe Fernandes; Camargo, Gabriela Maia [UNESP]; Adami, Jose Feliciano [UNESP]; Dias, Rubens Alves [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
The Ponto Iluminadoinitiative consists of a wide range of technical actions in the areas of clean energy generation, energy efficiency, solid waste management and water savings together, creating a virtuous cycle of sustainability within the Saõ Paulo State University-Guaratingueta campus. The development of this model campus serves as a large laboratory for the entire local community and, also, having already received visitors from all regions of the country; in order to disseminate the concepts of sustainability and create a more conscious society regarding the rational use of natural resources. This project, which achieves 12 of the 17 Sustainable Development Goals, aims to change actions and customs through education and improvement of knowledge, acting, especially, in the conscious education of children and young people. Thus, creating a society capable of growing and developing with greater care for the environment and being capable of a better managing of its natural resources.
Keywords: community; education; health; sustainability